DAYA SAING USAHA PENGGEMUKAN SAPI POTONG PETERNAKAN RAKYAT DI KABUPATEN BOJONEGORO, JAWA TIMUR - Retna Dewi Lestari; Lukman Mohammad Baga; Rita Nurmalina (Faculty of Animal Science, Universitas Gadjah Mada, 2017)
The purpose of this study was to analyze the competitiveness on beef cattle fattening small scale business in Bojonegoro. Data processing quantitative methods using PAM (Policy Analysis Matrix). Analysis of competitiveness calculated by the approach of comparative advantage (Domestic Resources Cost Ratio) and competitive advantage (Private Cost Ratio), based on the results of the research value of the DRC and PCR respectively 1,04 and 1,05, this result shows that fattening beef cattle in Bojonegoro not competitive. Policy implications that can be applied in order fattening beef cattle in Bojonegoro competitiveness is to increase ADBW (Added Daily Body Weight) amounted to 17,33 percent, equivalent to 0,11 kg per day from the previous ADBW 0,55 kg per day, one attempts to do is the provision of input quality feed and concentrates, as well as the necessary counseling to farmers about the importance of quality feed and to improve the ability of farmers needed training and assistance from the Government of Bojonegoro.